2021
DOI: 10.1038/s41419-021-03554-6
|View full text |Cite
|
Sign up to set email alerts
|

FoxP3-miR-150-5p/3p suppresses ovarian tumorigenesis via an IGF1R/IRS1 pathway feedback loop

Abstract: Ovarian cancer (OC) causes more deaths than any other gynecological cancer. Many cellular pathways have been elucidated to be associated with OC development and progression. Specifically, the insulin-like growth factor 1 receptor/insulin receptor substrate 1 (IGF1R/IRS1) pathway participates in OC development. Moreover, accumulating evidence has shown that microRNA deregulation contributes to tumor initiation and progression. Here, our study aimed to investigate the molecular functions and regulatory mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 74 publications
0
16
0
Order By: Relevance
“…It has been suggested that miR-150 may play a role in various types of tumor development. It is also associated with the regulation of ovarian cancer and the poor prognosis of NSCLC patients [ 41 , 42 ]. In the case of breast cancer, miR-150 is regulated by lncRNA MAFG-AS1.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that miR-150 may play a role in various types of tumor development. It is also associated with the regulation of ovarian cancer and the poor prognosis of NSCLC patients [ 41 , 42 ]. In the case of breast cancer, miR-150 is regulated by lncRNA MAFG-AS1.…”
Section: Discussionmentioning
confidence: 99%
“…Among the most significant 10 pathways, five were signal transduction pathways, including the MAPK signaling pathway, AMPK signaling pathway, PI3K-Akt signaling pathway, Estrogen signaling pathway, and Hippo signaling pathway. In particular, the PI3K/AKT/mTOR cascade has been identified as frequently altered in OVC ( 22 ). The three signaling pathways were all significantly disturbed by the diagnostic miRNAs, implying their important role in OVC.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, we identified three miRNAs, miR-150-3p, miR-297, and miR-27b, targeting CXCL10 and CXCL8, for which there was no previous information regarding an association with DM or CKD-related diseases or a relationship with lnc-SLC15A1-1. In literature reviews, the functions of miR-150-3p and miR-297 were related to cancer [66,67]. Moreover, miR-27b-5p exerted biological effects on HUVECs, fibroblasts, and breast cancer cells in previous reports [68][69][70].…”
Section: Discussionmentioning
confidence: 98%